The long-term impact of Objective 1 funding on unemployment and labour market disparities: Evidence from the UK - Marco Di Cataldo (European Regional Science Association (ERSA), 2015)
In the past years, a large number of evaluations have assessed the impact of European Union?s Cohesion Policy, the largest transnational programme for regional development promotion worldwide. In particular, great attention has been devoted to determine the effectiveness of EU funds in improving economic and labour market conditions in Objective 1 regions, the most economically disadvantaged areas receiving the large majority of the funds. However, there is no consensus yet in the literature on whether Structural Funds have successfully contributed to promote convergence by improving the economic performance of the poorest regions in the EU. In addition, a lot of attention has been devoted to determine the effect of Cohesion Policy interventions on inequality across regions and countries, but little research has been carried out to analyse the impact of the policy in reducing disparities within the targeted regions. In order to provide more conclusive answers on the effectiveness of Cohesion Policy, a new strand of evaluations has emerged in the literature. This research is based on the adoption of quasi-experimental methods to capture the causal effects of the policy. In this paper we follow this example and use a differences-in-differences strategy to estimate the impact of Cohesion Policy. By exploiting an exogenous change in eligibility for Objective 1 support occurred in the UK region of Cornwall in 2000, we are able to compare Cornwall?s unemployment trend before and after the introduction of Objective 1 support. The study is performed at three different geographical levels. First, we construct a synthetic control region that equals the treated region in all relevant characteristics except for not having received Objective 1 funding. Second, we use Local Authority Districts and compare the unemployment change of Cornwall with similar English areas. Third, we adopt propensity score matching techniques and estimate the average treatment effect at the level of electoral wards. All different methodologies provide clear evidence of a reduction in unemployment in Cornwall as compared to regions that did not benefit from Objective 1 support. In the second part of the study we identify the areas that experienced the highest unemployment change. We estimate the difference in quantile functions between Cornwall wards and control wards, constraining treatment and control to have the same unemployment distribution before the treatment. We find that the main variations occurred towards the higher end of the unemployment distribution, that is, for wards starting from a higher unemployment level. This suggests that labour market disparities have consistently reduced during the intervention period. We put forth some hypotheses to explain Cornwall?s successful management of EU funds.
Keywords: R11; O18; J60; 330; EU Cohesion Policy; Objective 1; unemployment; labour market disparities; UK